PERANCANGAN SISTEM INFORMASI PENJUALAN PADA PT. ERA WINON INTER AGDEV MEDAN DENGAN METODE STRADIS - Erikson Damanik; Mushtafa Haris Munandar; Meylida Girsang; Toras Pangidoan Batubara; Muhammad Faisal (Politeknik Bisnis Indonesia, 2024)
This research aims to design and analyze a computerized sales information system at PT. Era Winon Inter Agdev Medan, a company distributing pesticides, fertilizers, and seeds. Currently, the company's sales system is not integrated, causing operational control difficulties and delays in providing managerial information. Using the STRADIS method, this research involves an initial organizational study, analysis of the existing system, and design of alternative solutions using DFD diagrams. Data collection methods include observation, interviews, and document studies. The results include a new system design featuring various input, search, and report forms that can process sales data in real-time, accelerate information processing, and improve accuracy in strategic decision-making. The implementation of this system has proven to enhance operational efficiency, facilitate inventory and receivables management, and improve customer service quality. Overall, the computerized sales information system significantly contributes to PT. Era Winon Inter Agdev Medan's competitive advantage in the market.